The THAM’s, portuguese version of Mat's - assessment/intervention metalinguistic awareness resource - Figueira, Ana Paula Couceiro (2022)
We present resources for assessment and intervention at the level of metalinguistic awareness provided for three distinct and specific age groups: children, adolescents and adults. We rehearsed the Portuguese version of the MAT's (Metalinguistic Ability Test), the THAM’s (Testes de Habilidades Metalinguísticas), the THAM1, THAM2 and THAM3. The THAM - 1, for children from 4 - 6 years old garden for children's transition to school the 1st cycle of basic education, the THAM - 2, for children from 9 - 13 years of age 1 transition to the 3rd cycle, and the THAM - 3, for adolescents and adults, in the transition from secondary to higher education.